Verifying compositional equivalence between web service composition graphs. (30th January 2018) - Rai, Gopal N.; Gangadharan, G. R.
Summary: Given a composition request, the formation of possible Web Service Composition Graphs (WSCGs) depends on the set of available services. Since the availability of Web services is dynamic, at any time, a new service can join or an existing service can leave the set of available services. A change in the set may bring the structural change in a previously formed WSCG. However, it is not always the case that a structural change in the WSCG brings the semantic change. In this paper, our aim is to verify the compositional equivalence between two WSCGs formed before and after the structural change caused by the change in the set of available services. Our proposed solution is based on an algebraic formalism, and by using the formalism, directed acyclic WSCGs are formed for a given composition request. Then, by using WSCGs, we propose the concept of composition expression and canonical composition expression . On the basis of the proposed concept of canonical composition expression, we verify compositional equivalence between two WSCGs. The advantage of our approach is that it reduces the equivalence verification to the subsumption checking between two algebraic expressions instead of directly using the WSCGs and solving a subgraph matching problem. The proposed mechanism is implemented and evaluated for the exhaustive possibilities in a travel agency case study with respect to a given composition request.